Effect Of Urea And Phenol Formaldehyde Resin Impregnation On Properties Of 7-Year-Old Kelempayan (Neolamarckia Cadamba) Wood - Mahmud, Siti Zalifah (2020)
The aim of this study was to determine the fundamental features of the 7-year-old kelempayan wood based on the different height level namely lower, center and upper. Besides that, the study determined the characterization of the 7-year-old kelempayan wood and analyzed the properties of a resin-impregnated wood